2004
DOI: 10.1017/s0950268804003292
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of F4+ E. coli in groups of early weaned piglets

Abstract: SUMMARYThe aim of this study was to estimate transmission parameters of enterotoxigenic F4+ Escherichia coli F4 (F4+ E. coli) in groups of early weaned piglets with F4-receptor-positive (F4R+) and F4-receptor-negative piglets (F4Rx). Transmission of F4+ E. coli was quantified in four heterogeneous groups of F4R+ and F4Rx piglets. Infectiousness was determined by the number of F4+ E. coli/g faeces shed during 8 days. Transmission parameters were estimated using generalized linear models assuming a stochastic SI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 21 publications
(22 reference statements)
0
11
0
Order By: Relevance
“…Variation in infectivity between individuals has shown to be of importance for the course of an epidemic [1-3] and can be associated with variation in clinical signs [4-6]. For some diseases, effective control measures should therefore target the severely diseased individual to reduce the size of an outbreak [7].…”
Section: Introductionmentioning
confidence: 99%
“…Variation in infectivity between individuals has shown to be of importance for the course of an epidemic [1-3] and can be associated with variation in clinical signs [4-6]. For some diseases, effective control measures should therefore target the severely diseased individual to reduce the size of an outbreak [7].…”
Section: Introductionmentioning
confidence: 99%
“…In three of the four infected animals, rotavirus was detected in their feces. Determination of the percent dry matter showed that only the fecal samples collected 18 hpi (piglets 65 and 67) had a significantly lower (pasty) consistency [ 18 ]. This indicated that not all of the piglets developed diarrhea before 12 hpi, and that the two piglets slaughtered 18 hpi did not develop the severe form of diarrhea normally observed at 24 hpi [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“… a The consistency of the feces was classified [ 18 ] as normal, unformed or loose, pasty, or fluid, by determining the percent dry matter (% dm). Feces samples were tested for the presence of rotavirus by ELISA [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rota virus predisposes the challenged animals to ETEC infection (Melin and Wallgren, 2002;Benfield, et al, 1988;Cox, et al, 1988;Sarmiento et al, 1988;Geenen et al, 2005). While a viral challenge can lower the resistance of the animal to an ETEC infection (this is a likely scenario in the field), doing so adds a confounding effect in studies examining interventions for ETEC caused PWD.…”
Section: Inadvertently or Intentionally Exposing Animals To Transmissmentioning
confidence: 99%